Theory of Planned Behavior: Determinants of the Use of Modern Family Planning Method - Agus, Yuliana; Pamungkasari, Eti Poncorini; Soemanto, RB. (Journal of Maternal and Child Health, 2019)
Background: The use of contraception tool is one of the factors that affect fertility. It is influenced by demographic, socio-economic, legal, political and environmental factors. The use of modern family planning method can provide optimal benefits by minimizing side effects and complaints felt by the community. The aim is to analyze the determinants of the use of modern family planning method in Malinau District, North Kalimantan by using the theory of planned behavior.Subjects and Method: This was an observational analytic study with cross sectional approach conducted in 4 (four) sub-districts in Malinau District, North Kalimantan, in December 2018 to January 2019. Total 200 subjects were selected by fixed disease sampling. The dependent variable was the mothers who applied the modern family planning method. The independent variables were maternal age, parity, area of residence, level of education, family income, perception, intention, attitude, and subjective norms. The data were collected by questionnaires and analyzed with path analysis.Results: The use of modern family planning method in women is directly and positively influenced by parity ≥ 4 (b = 3.03; 95% CI = 1.23 to 4.83; p <0.001), high family income (b = 4.57; 95% CI = 2.66 to 6.47; p <0.001), positive attitude (b = 3.92; 95% CI = 1.42 to 6.42; p = 0.002), and strong intention (b = 4.84; 95% CI = 2.85 to 6.82; p <0.001). The use of modern family planning method for women is indirectly influenced by the level of education and subjective norms.Conclusions: The use of modern family planning method in women is directly and positively influenced by parity ≥ 4, high family income, positive attitude, and strong intention. The use of modern family planning methods for women is indirectly influenced by the level of education and subjective norms.Keywords: modern contraceptive methods, Theory of Planned BehaviorCorrespondence: Yuliana Agus. Masters Program In Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36 A, Surakarta 57126, Central Java. Email: yulianaagus07@gmail.com. Mobile: 085343928921Journal of Maternal and Child Health (2019), 4(5): 369-379https://doi.org/10.26911/thejmch.2019.04.05.11